Research progress and management strategies of fungal diseases in Camellia oleifera - Chen, Xingzhou; He, Yuan; Wang, Zhikai; Niu, Anqi; Xue, Yi; Zhou, Diao; Zhou, Guoying; Liu, Junang (Frontiers in Microbiology, 2023)
Camellia oleifera Abel, a woody oil plant, that is endemic to China. Tea oil, also referred to as "oriental olive oil," is a superior quality plant-based cooking oil. The production of tea oil accounts for 8% of the total edible vegetable oil production in the country. Since 2022, the annual output value of C. oleifera industry has exceeded 100 billion yuan, making it one of the major economic contributors to China's rural revitalization development strategy. In recent years, demand and production have grown in parallel. However, this has led to an increase in the incidence levels of pest and diseases. Pests and diseases significantly reduce the quality and yield of C. oleifera. C. oleifera diseases are mainly caused by pathogenic fungi. C. oleifera anthracnose, soft rot, leaf spot, coal stain, leaf gall disease, and root rot are the most important fungal diseases affecting the C. oleifera industry. However, the same disease may be caused by different pathogenic fungi. C. oleifera can be found in half of China and is found in several climatic zones. The geographical distribution of woody plant diseases is consistent with the distribution of the tree species and the ecology of the range, which also results in a highly complex distribution of fungal diseases of C. oleifera. The management of fungal diseases in C. oleifera is extremely challenging due to the variety of pathogenic fungal species, multiple routes of transmission, the lack of resistant plants, and the environmental safety of chemical measures.